Language is the core of every nation's culture, the sacred mirror of the nation's spirituality - Majidova, Laylo; Karshiyevna , Muminova Umida (PT. Antis International Publisher, 2024)
This article talks about the legal status of the Uzbek language, the preservation of the language and its further development, as well as our writers and intellectuals who made a great contribution to the development of the Uzbek language.